2022
DOI: 10.1037/aca0000515
|View full text |Cite
|
Sign up to set email alerts
|

The spectrum of distributed creativity: Tango dancing and its generative modalities.

Abstract: As scholars have recently emphasized, creativity is not restricted to the individual mind; it can happen in and through interaction. To evaluate the legitimacy of claims about “distributed creativity,” we propose a compare-and-contrast approach to Argentine tango. Tango is an improvisational leader–follower dance of a formally constrained kind, yet one that also allows for a range of modes of being creative together in real-time interaction. Six dance couples were filmed while improvising and subsequently inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 89 publications
0
6
0
Order By: Relevance
“…We have shown that moments that afford immediate creative action exist, but in others “the creative” is only the attribute of an extended practice. This suggests starting the analysis from affordance-mediated creative activity (Kimmel & Groth, 2023) rather than narrowly conceived “creative affordances.” This activity is always relative to multi-timescale engagement with the ecology, from which emergent system dynamics arise.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…We have shown that moments that afford immediate creative action exist, but in others “the creative” is only the attribute of an extended practice. This suggests starting the analysis from affordance-mediated creative activity (Kimmel & Groth, 2023) rather than narrowly conceived “creative affordances.” This activity is always relative to multi-timescale engagement with the ecology, from which emergent system dynamics arise.…”
Section: Discussionmentioning
confidence: 99%
“…The affordance field that presents itself emerges "transactionally" and cannot be attributed to either of the individuals (cf. Kimmel & van Alphen, 2022). Since creative opportunities are caused by the reciprocal engagement a methodologically individualist analysis is inadequate.…”
Section: Interaction-based Emergence Problem Generation and Risk Mana...mentioning
confidence: 99%
See 3 more Smart Citations